A mixed approach to understanding sustainable entrepreneurial intention. Issue 3 (November 2022) - Truong, Hue Thi; Le, Thao Phuong; Pham, Hang Thi Thanh; Do, Duc Anh; Pham, Thuy Thu
Abstract: Entrepreneurship and sustainable development have been extensively debated; however, research on sustainable entrepreneurial intention (SEI) is still in its infancy. This article investigates the sociological and psychological aspects of the theory of planned behaviour (TPB) that influence students' SEI. A survey dataset with 621 observations was collected from six higher education institutes in the North of Vietnam, and partial least squares structural equation modeling (PLS SEM) was applied. The results indicate that perceived behaviour control influenced the intention to start a sustainable entrepreneurship (SE) the most, followed by personal attitude. Subjective norms were found to be the only one of the three TPB factors that was not an antecedent for sustainable entrepreneurial intention. Education and family support contributed significantly to the favourable attitudes toward SE. However, education and social support had no relation to perceived behaviour control. In the context of a developing country like Vietnam, this research offers a significant contribution, as there is an urgent need for SE studies outside of developed nations. Highlights: Understanding of sustainable entrepreneurial intention (SEI) is limited in literature. Studies on entrepreneurial intention is mostly based on psychological approach based. We investigated SEI's drivers by a new approach, combining psychological and social factors.